Communicative conditionality of gender identity in social and philosophical dimension - Svitlana Zagurska (Cхід, 2016)
The essential factors of implementation of gender identification in the context of social and communication interaction have been considered in terms of the social and philosophical analysis. The author focuses on the achievements of postmodern philosophy in terms of the scientific analysis that focused on the problem of understanding gender marking subjectivity not as immutable biological forms but as socially constructed conducted by certain types of social and communicative strategies. The author indicates that different social aspects of biological sex of the individual associated with the process of public perception and the system of established socio-cultural relationship. These require the individual to a particular type of gender communicative behavior, the most appropriate in a particular society, and language becomes from an external tool in a tool of external means of formation of subjectivity, begins to define the essential contents of the subject. Language appears not only a way of individuals communication, but it is also organic strategy "involvement" of the subject in contemporary culture system, it acts as the key to his self-expression and identity. The author emphasizes that gender role is a differentiation of activity, status, rights and duties of individuals based on their gender; it belongs to the category of social roles and expressing certain social expectations. The value-regulatory system family (patriarchal or egalitarian), which brought up a specific person, has an influence on the formation of gender roles. In terms of the communication gender display is means of gender roles implementation. Gender identity should not be seen as attributive property of the individual, but it should be seen as a model of social and communicative behavior, that enables selection of the most effective communication strategies for social interaction and social causes of self-identity. This idea is emphasized in the conclusions.